Detection of Paraffin Oil Adulteration in Edible Oils Using FTIR Spectroscopy - Bunaciu, Andrei A.; Aboul-Enein, Hassan Y. (Pharmaceutical Research: Recent Advances and Trends Vol. 9, 2024)
Edible oils are commonly used as salad, cooking or frying, or in fabricating food products. From the standpoint of nutrition, they are major, but there has been concern over their purity from ancient times. Adulterating high-priced oil with low-priced oil is a significant problem due to its increased demand in domestic and foreign markets. Customers' health may suffer as a result. Therefore, authentication and adulteration prevention are urgently needed for customers' benefit. The application of mid-infrared or near-infrared spectroscopy of molecular vibrations has become more prevalent in the characterization of various chemicals, such as edible oil, intending to track alterations and identify counterfeit modifications. A novel method to assess the alteration of rapeseed oil (RSO), sunflower oil (SFO), maize germ oil (CGO), and extra virgin olive oil (EVOO) with mineral oil, paraffin oil (PO), was established. Using ATR spectra, a Fourier transform infrared (FT-IR) spectrometric technique was created to evaluate edible oil adulteration quickly. The findings show that the suggested approach effectively detects paraffin oil in adulterated EVOO, SFO, RSO and CGO.